Kampung Ramah Lansia sebagai Pendekatan Kota Tangguh dalam Mendukung Pencapaian Tujuan Pembangunan Berkelanjutan - Soni Pratomo; Oktiara Nazela; Nurhayati Nurhayati; Harlia Febrianti (Jurnal Daur Lingkungan, 2023)
Senior Citizen in Jambi Province has approached 10% which is the demographic limit of the aging population. The Jambi Provincial Government in the Jambi Province Medium-Term Development Plan has a strategic program for the Elderly Village. The Elderly Village or Senior Citizen Village does not yet have a clear concept in the document. In this regard, this research is conducted to offer the concept of planning for the Elderly (friendly) Village so that it can be applied in the development of Jambi Province. In line with the eleventh Sustainable Development Goals, the question of this research is how the concept of an elderly-friendly village is to create a resilient and sustainable city in Jambi Province. This study aims to create the concept of Senior Citizen Village in Jambi Province. The targets achieved in this study were identification of the activities and space requirements of the Elderly Friendly Village, identification of the morphology of Senior Citizen Village and investigation of the space requirements of Senior Citizen Village in supporting the Resilient City in Jambi Province. This study used descriptive qualitative method. Data in the form of maps, pictures or interviews will be analyzed by content analysis. The results of the analysis show that it is still possible to add open space for elderly activities that support the realization of a Resilient City in Jambi Province.